2022
DOI: 10.1530/ec-22-0250
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of endocrine disease in sphingosine-1-phosphate lyase insufficiency: case series and literature review

Abstract: Sphingosine-1-phosphate lyase (SGPL1) insufficiency syndrome (SPLIS) is an autosomal recessive multi-system disorder, which mainly incorporates steroid-resistant nephrotic syndrome and primary adrenal insufficiency. Further variable endocrine manifestations are described. We aimed to comprehensively annotate the endocrinopathies associated with pathogenic SGPL1 variants and assess for genotype-phenotype correlations by retrospectively reviewing reports of endocrine disease within our patient cohort and all pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Children presenting early in life had a more severe clinical presentation with primary adrenal insufficiency or steroidresistant nephrotic syndrome being seen in the early postnatal period. Overall mortality rate is high, approaching 47% (17).…”
Section: Discussionmentioning
confidence: 99%
“…Children presenting early in life had a more severe clinical presentation with primary adrenal insufficiency or steroidresistant nephrotic syndrome being seen in the early postnatal period. Overall mortality rate is high, approaching 47% (17).…”
Section: Discussionmentioning
confidence: 99%
“…The rst reports of the monogenic cause of this condition in 2017 focused on two of the most common clinical features, namely steroid-resistant nephrotic syndrome (often associated with focal segmental glomerulosclerosis pathology), and primary adrenal insu ciency [5 6]. Adrenal insu ciency may include low glucocorticoids with or without low mineralocorticoids, and in boys may also include low testosterone levels leading to gonadal dysgenesis [7]. Other effects observed in SPLIS patients include peripheral neuropathy, central nervous system involvement, immune dysfunction, hypercholesterolemia, and ichthyosis or acanthosis [5 6 8 9].…”
Section: Introductionmentioning
confidence: 99%
“…54 However, Maharaj et al found 50 cases and identified a 64% prevalence of AD. 68 Novel SGPL1 mutation has been reported in relationship with pediatric presentation without hyperpigmentation. 69 More than 200 NR0B1 mutations have been recorded so far.…”
mentioning
confidence: 99%